If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2c(c-3)=11(4)
We move all terms to the left:
2c(c-3)-(11(4))=0
determiningTheFunctionDomain 2c(c-3)-114=0
We multiply parentheses
2c^2-6c-114=0
a = 2; b = -6; c = -114;
Δ = b2-4ac
Δ = -62-4·2·(-114)
Δ = 948
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$c_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$c_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{948}=\sqrt{4*237}=\sqrt{4}*\sqrt{237}=2\sqrt{237}$$c_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-2\sqrt{237}}{2*2}=\frac{6-2\sqrt{237}}{4} $$c_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+2\sqrt{237}}{2*2}=\frac{6+2\sqrt{237}}{4} $
| 7x-3=4x-18 | | 16x+14/3-15x=1/6 | | x+1=18-2x | | -7x-7=-43-x | | 4+6(w+2)+w=0 | | x^2-(x+1)^2=25 | | 4+6w+12=6w | | 7x+6=-x+30 | | 1/2(4a+8)=-2a+4 | | 3+6(x-2)=45 | | 2/3x+3=-4x+17 | | -4x+3=-3x+8 | | -5x-2+-10=5x-2-30 | | 10+4x=5(x-6)+30 | | 4n=3+15 | | 15-4=12y-28 | | x+4=46-5x | | 1/2(x-124)=13+8x | | 5.65x+28.25=56.5 | | h+1.6=4 | | −6y+3=−3 | | 34(4x–8)=18 | | -5r+-13=9r+8 | | Y=270=27x | | -16.44=-4.9x-1.4-7.2 | | -5(3x-25=2(x-11)-57 | | 5b-35=5b-35 | | 34+4x=5(-x+2)-21 | | 6c+-6c−20c=20 | | (3x+31)=(2x-6)=180 | | 4(p+5)=6p+30 | | 6c+-6c−-20c=20 |